Analysis of Efforts in the Development of Local Government: E-Government and Public Service Management - Firman, Firman; Sahrul, Sahrul; Ramadoan, Syahri (Department of Government Studies, Universitas Muhammadiyah Buton., 2023)
This study aimed to determine the efforts to develop e-government and improve public services in Bima Regency. This research used descriptive qualitative methods. The subjects of this research were selected through a nonprobability sampling technique using a purposive sampling technique. The informants in this study were 20 web admins of Bima Regency Government institutions. Data collection techniques consisted of observation, interviews, and documentation. The results showed that support for implementing e-government in public services in Bima Regency has been provided. However, it could be more optimal due to different budget allocations in each local government agency. Regarding capability, in general, the literacy level of Bima Regency Government employees still needs to improve, especially senior employees. Meanwhile, in terms of value, e-government managers already understand the benefits and importance of information technology applications in public services. For e-government implementation to run optimally, creating a clear legal umbrella and making a grand design for e-government development, including preparing the budget, is necessary. Related to employees who still need to improve in literacy, it is essential to plan continuous Information Technology training, and in the future, the Bima Regency government should plan to recruit employees with an educational background in information technology.